Land financialisation, planning informalisation and gentrification as statecraft in Antwerp. (July 2022) - Ward, Callum
This article offers insight into the role of the state in land financialisation through a reading of urban hegemony. This offers the basis for a conjunctural analysis of the politics of planning within a context in which authoritarian neoliberalism is ascendant across Europe. I explore this through the case of Antwerp as it underwent a hegemonic shift in which the nationalist neoliberal party the New Flemish Alliance (Nieuw-Vlaamse Alliantie; N-VA) ended 70 years of Socialist Party rule and deregulated the city's technocratic planning system. However, this unbridling of the free market has led to the creation of high-margin investment products rather than suitable housing for the middle classes, raising concerns about the city's gentrification strategy. The consequent, politicisation of the city's planning system led to controversy over clientelism which threatened to undermine the N-VA's wider hegemonic project. In response, the city has sought to roll out a more formalised system of negotiated developer obligations, so embedding transactional, market-oriented informal governance networks at the centre of the planning system. This article highlights how the literature on land financialisation may incorporate conjunctural analysis, in the process situating recent trends towards the use of land value capture mechanisms within the contradictions and statecraft of contemporary neoliberal urbanism.